Adaptação e validação do evidence-based practice attitude scale (EBPAS) - Moreno, Regina Célia Barbosa (2015)
Nowadays, there is a tendency for the Health Services to demand changes both in the professional practices and in the management in order to improve the organizational performance. In a hospital organization, the Social Service doesn`t remain free from this demand, and this scenario took us to the following question: How to adapt the Evidence-Based Practice Attitude Scale (EBPAS) to the Brazilian Health Social Service, and how to validate it? Thus, this research aims to adapt e validate the Evidence-Based Practice Attitude Scale (EBPAS) to the Brazilian Health Social Service, and it offers a version for EBPAS which can measure the social worker`s attitude related to the systematization of the professional practices; such version can be useful for future studies related to the elaboration of social protocols. The present research works based on the methodology proposed by Beaton, Bombardier, Guillemin & Ferraz (2000); Beaton, Bombardier, Guillemin & Ferraz (2007). The translation and adaptation process contains five steps: (i) translation, (ii) back translation, (iii) synthesis of the translations, (iiii) evaluation by an expert commitee and (iiiii) pretest. For the psychometric validation, the results presented suggests that the instrument presents a convergent validation, and it can be considered a useful instrument to measure the social workers` attitude related to the adoption of the Evidence Based Practice, making possible its use in the health services when the professionals` readiness related to the implementation of innovative practices has to be measured. The instrument presented easy comprehension and showed also semantic, idiomatic, experimental and conceptual validation. It is evident the need to broaden the fields of the psychometric validation, as well as to diversify the sampling plan.